2021
DOI: 10.1075/jicb.19027.ber
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating, communicating, and combining languages in local immersion education policy reform in Finland

Abstract: The aim of this article is to examine local enactment of new curriculum policy, paying special attention to combining the language of instruction in the school (Finnish) and the immersion language (Swedish) in an early total one-way Swedish immersion programme in Finland at a programmatic level. The study combines ethnography with educational language policy by focusing on coordinative and communicative discourses surrounding local immersion curriculum. The participatory observation data consist of 36 hours of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…We are not aware of other studies that have specifically analysed subject-related lexical acquisition, but the results are consistent with studies that consider the general development of L1 proficiency, in which lexis is a key element, carried out in other contexts by Bergroth [59] or Merisuo-Stomr [31] and in our context, by Barrios [32], although at different educational levels. These studies show that the fact of taking immersion or bilingual programmes does not negatively affect the L1 proficiency of students in these programmes.…”
Section: Discussionsupporting
confidence: 88%
“…We are not aware of other studies that have specifically analysed subject-related lexical acquisition, but the results are consistent with studies that consider the general development of L1 proficiency, in which lexis is a key element, carried out in other contexts by Bergroth [59] or Merisuo-Stomr [31] and in our context, by Barrios [32], although at different educational levels. These studies show that the fact of taking immersion or bilingual programmes does not negatively affect the L1 proficiency of students in these programmes.…”
Section: Discussionsupporting
confidence: 88%
“…During the pre-service teacher education, one of the participants had oriented towards immersion, while the others had gained their immersion knowledge through in-service training (cf. Bergroth, 2015;Bonilla, 2017). We concluded that the general teacher education neither prepared student teachers for immersion instruction nor gave them an immersion teacher identity (see also Alisaari et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…The socialisation in working life consisted of instructional and relational aspects, as well as advocacy. Instructional socialisation related to awareness of language(s) and to lack of materials (see also Bergroth, 2015;Peltoniemi et al, 2018). The need for additional pedagogical and linguistic planning started immediately when entering the profession and continued throughout their career.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation